Telemedicine efficacy and satisfaction of patients and headache specialists in migraine management - Liu, Qinlin; Liu, Fang; Yu, Xiran; Zang, Jiali; Tan, Ge (Frontiers in Molecular Neuroscience, 2023)
Background: Migraine follow-up is difficult for outpatients, especially after the COVID-19 pandemic, we tried to identify the most appropriate telemedicine methods for migraine in terms of efficacy, safety, patient compliance, and patient and physician satisfaction. Methods: Migraine patients were screened from the Headache Center of the First Affiliated Hospital of Chongqing Medical University from September 2019 to December 2021 and randomly classified into an outpatient group and four telemedicine groups: social software, telephone, E-mail, and short message. Headache specialists followed up with the patients 3 and 6 months after their visit and asked about their satisfaction with the follow-up in each instance, as were the headache specialists. Results: A total of 147 migraine patients were included, of whom 65 completed the follow-up. After 3 and 6 months of follow-up, the proportion of patients whose monthly headache frequency decreased by over 50% in the social-software, telephone, and E-mail groups was no different from that in the outpatient group. A similar result was obtained from evaluations with the Visual Analog Scale, the Headache Impact Test, and the Migraine Disability Assessment compared with baseline in social software and telephone groups. The compliance in social-software group was not worse than that in the outpatient group. The proportion of patients in the E-mail group who completed the follow-up and the proportion of patients in the telephone group who consistently took preventive medication were significantly lower than those in the outpatient group. After 6 months, the majority of patients in the outpatient, social-software, and telephone groups and headache specialists in the outpatient, social-software groups were satisfied with the follow-up, while fewer patients in the E-mail group and fewer specialists in the telephone and E-mail group showed their satisfaction. Conclusion: Compared with outpatient visits, it is safe and effective to use social software and telephone to follow up on migraine patients, and E-mail and short-message follow-up have lower feasibility. Migraine patients prefer social-software and telephone follow-up, while specialists prefer social-software follow-up.